An assessment of the economic viability of mining the UG2 Reef within the no.12 Shaft lease area, Impala Platinum Limited - Theart, H.F.J. (University of Pretoria, 2013)
Dissertation (MSc (Earth Science Practice and Management))--University of Pretoria, 2008.